2021
DOI: 10.1016/j.jinf.2021.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence of SARS-CoV-2 reinfection case with the emerging B.1.2 variant in Brazil

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These variants have a common mutation N501Y in the S protein receptor-binding domain (RBD), except the Delta variant, which results in the greater affinity of their S protein for ACE2, enhancing viral attachment and subsequent entry into host cells ( Kemp et al, 2020 ; Barton and MacGowan, 2021 ). The emergence of the novel variants has been particularly of great concern ( Rahman et al, 2021 ) since recently published data suggest that previous infections with SARS-CoV-2 may not protect an individual from new variants of SARS-CoV-2 giving rise to reinfection cases in the community ( Fonseca et al, 2021 ). Therefore, it is important to elucidate the genetic information of SARS-CoV-2 cases for clinical and therapeutic management.…”
Section: Introductionmentioning
confidence: 99%
“…These variants have a common mutation N501Y in the S protein receptor-binding domain (RBD), except the Delta variant, which results in the greater affinity of their S protein for ACE2, enhancing viral attachment and subsequent entry into host cells ( Kemp et al, 2020 ; Barton and MacGowan, 2021 ). The emergence of the novel variants has been particularly of great concern ( Rahman et al, 2021 ) since recently published data suggest that previous infections with SARS-CoV-2 may not protect an individual from new variants of SARS-CoV-2 giving rise to reinfection cases in the community ( Fonseca et al, 2021 ). Therefore, it is important to elucidate the genetic information of SARS-CoV-2 cases for clinical and therapeutic management.…”
Section: Introductionmentioning
confidence: 99%
“…The alpha variant carries E474K and L452R mutations in the spike protein, as well as D3L, R203K, S235F, and G204R in NP [27]. Lineage B.1.2 contains a Q667P mutation in the spike protein and P199L and P67S mutations in NP [28]. Both authentic virus variants could be recognized by NP-mAb-40/7 LFIA strips (Figure 3C).…”
Section: Screening Of Antibody Pairs In Lateral Flow Immunoassays (Lfias) To Detect Np Antigenmentioning
confidence: 97%
“…A study conducted in the United Kingdom (UK) identified possible reinfections in 0.7% (95% CI 0.6-0·8%) of individuals infected during September-December 2020 and found no evidence that the frequency of reinfections was higher for the VOC Alpha than for pre-existing non-VOCs 19 . In Brazil, previous studies documented a few cases of reinfection with lineages B.1.1.28, B.1.1.33 and B.1.2 20-22 , with lineage P.2 that harbors the mutation S: E484K 23,24 and with the VOC Gamma 17,18 . However, there is no evidence that reinfections with Gamma were more frequent than with non-VOCs.…”
Section: Introductionmentioning
confidence: 97%